The impact of curriculum changes on english language teaching - Auladi, Ifan Rikhza (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Curriculum reform plays a crucial role in shaping the quality of education and determining how learning is conceptualised and delivered. In Indonesia, curriculum changes have been frequent, reflecting the government’s attempt to balance local needs with global demands. The most recent reform, the Emancipated Curriculum (EC), was introduced in 2022 to promote learner autonomy, communicative competence, and project-based learning, especially in English Language Teaching (ELT). This conceptual study adopts an integrative literature review approach to synthesise theories and previous studies on curriculum reform and its impact on ELT. The analysis highlights that the EC offers significant opportunities, including the adoption of Communicative Language Teaching (CLT), learner-centered innovation, and contextualised instruction. However, challenges persist, such as limited teacher readiness, resource constraints, and students’ difficulty in adapting to independent learning. The discussion integrates Change Theory, Sociocultural Theory, and Constructivist Learning Theory to explain how curriculum reform can be enacted meaningfully in ELT. Findings suggest that successful reform requires policy alignment, continuous professional development for teachers, student engagement, and institutional support. This study contributes to both theory and practice by offering a conceptual model of responsive ELT in Indonesia and proposing directions for future research.